Studi Literatur Kesiapan Remaja Memasuki Perguruan Tinggi - Derry Kurniawan; Rakhmi Mashita (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2020)
The purpose of this study is to construct a stronger conception of adolescents’ readiness before college or college readiness, so that they can add to literature from domestic journals. The method in this research uses literature studies, using descriptive analysis techniques of literature data. Sources of data in the study came from 83 literatures using articles, journals and books related to college readiness. The results of the data source analysis show that the definition of higher education readiness is an individual’s readiness that is influenced by multidimensional strengths personal and interpersonal, are transitional in nature and can explain the reference point for their readiness before entering college. In summary, the concept of higher education readiness is divided into two factors, namely internal factors and external factors. Internal factors include self-potential, motivation, conditions, and costs. Meanwhile, external factors include the social environment, expectations and opportunities, information communication, and institutions. The impact caused by the readiness of adolescents before college leads to several variables which are divided into three domains, namely individual performance, academic performance, and benefit capitalization.